Intraoperative localization of gastrointestinal tumors by magnetic tracer technique during laparoscopic‐assisted surgery (with video). (2nd December 2021) - Lu, Guifang; Li, Jing; Yan, Xiaopeng; Sun, Xuejun; Yin, Yan; Lu, Xinlan; Ma, Feng; Ma, Fei; Zheng, Jianbao; Zhao, Wei; Lv, Yi; Ren, Mudan; et al.
Abstract: Background: Laparoscopic localization of gastrointestinal tumors has long been an important objective. This study aimed to evaluate the clinical application of a magnetic tracer technique during laparoscopic-assisted surgery. Methods: Fifty-seven patients with gastrointestinal tumors, who voluntarily underwent endoscopic marking between May 2019 and May 2020, were enrolled. A magnetic ring was clamped onto tissues adjacent to the lesion and released during preoperative endoscopy. Then, another magnet ring or laparoscopic instrument was delivered to the wall of the digestive tract contralateral to the lesion and attracted, thus achieving accurate intraoperative localization. Observational evaluation included data regarding preoperative marking, intraoperative localization, operation, and safety. Results: Fifty-six of the 57 (98.2%) patients with gastric tumors ( n = 35), duodenal tumors ( n = 1), and colorectal tumors ( n = 20), successfully underwent marking, localization, and resection. The mean margins of proximal and distal resection of colorectal tumors were 106 and 78 mm, respectively. The mean (± SD) duration of endoscopic marking and laparoscopic localization for gastric/duodenal and colorectal tumors were 5.3 ± 0.3, 1.0 ± 0.1, 5.5 ± 0.4, and 1.0 ± 0.1 min, respectively. No complications occurred in 56 of the 57 patients. Conclusions: The magnetic tracer technique demonstrated promising potential as a localization method for gastrointestinal tumors, with superior safety, effectiveness, rapidity, and convenience.